Le paradigme de l’absence dans l’œuvre de Jean Muno - Bizek-Tatara, Renata (Quêtes littéraires, 2011)
In the works of Jean Muno the absenteeism theme has got diffrent features and forms. Escape from grey and sad reality to world of imagination is the best way to deal with mental and physical absenteeism: weary figure is looking for loneliness away from his everyday reality. He wants to dream and reflect in peace and quite. The absence has been showed as a lack, also has been presented in the perspective of ontological. Characters created by J. Muno have personality problems cause by time reality and society. Society determined who character should become. All efforts being yourself ends failure. Muno in his works presents french speakers Belgians, called la belgitude. Heroes of Muno have problem with find them national identity, they suffer because of double culture. They are able to accept and take advantage of this situation.